Call for implementing a radiation protection culture in fluoroscopically guided interventional procedures - Bartal, Gabriel (2016)
The purpose of this article is to discuss the first prospective study published to date that followed a large cohort of radiologic technologists; the authors examined the risks of cancer incidence and mortality in U.S. radiologic technologists (radiographers) assisting in fluoroscopically guided interventional procedures.